Social Innovation as a platform for hybridizing Education Systems - Carrera, Dario; Boyaci, Melih; Caprioli, Domenico Maria (Community Notebook. People, Education and Welfare in the Society 5.0, 2023)
The connection between social innovation and education crosses the domain of technology in a wide and composite field. The development of new digital tools for content creation - including the no-code authoring tools - and the capability to create low-cost and highly replicable learning environments has been generating the birth of social and innovative enterprises, providing non-formal education, complementary to the public education system.